The Influence of Self Efficacy on Learning Outcomes in E-learning Activities with Learning Motivation as Moderator - Gumelar, Satya Fajar; Sary, Fetty Poerwita (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
Who conducted this research on students of the Faculty of Business Economics, Telkom University Class of 2017 to know how the influence of self-efficacy (X) on learning outcomes (Y) during the e-learning period with learning motivation (Z) as the moderator variable. In this study, the authors collected data using a questionnaire with a total sample of 285 respondents and used probability sampling with a simple random sampling method. The data analysis technique used is quantitative analysis with linear regression and multiple linear regression methods with moderating variables using the IBM SPSS Statistics program. The results showed that self-efficacy (X) partially affected learning outcomes (Y), and simultaneously learning motivation (Z) and self-efficacy (X) influenced learning outcomes (Z) during the e-learning period. We can conclude that self-efficacy (X) can improve learning outcomes (Y) during the e-learning period. Still, when coupled with high learning motivation (Z), it will increase the relationship of self-efficacy (X) to learning outcomes. (Y) so that it can further improve learning outcomes during the e-learning period for students of the 2017 Faculty of Business Economics, Telkom University.